(untitled) (Emergency Care Journal, 2026)
Tuberculous meningitis is a rare but severe form of extrapulmonary tuberculosis, often diagnosed late due to its subacute and non-specific clinical symptoms. This report describes a 42-year-old immunocompetent man with tuberculous meningitis, diagnosed in the emergency room, presenting with acute hydrocephalus and typical basal meningeal enhancement on MRI. PCR confirmed the diagnosis for Mycobacterium tuberculosis on gastric aspirate. Early treatment with antituberculosis drugs, corticosteroids, and neurosurgical intervention led to a positive outcome. This case emphasizes the importance of maintaining a high index of suspicion for tuberculous meningitis, even in immunocompetent patients, and highlights the need for early multidisciplinary management to reduce mortality and neurological complications.